Penyaiapan Guru Agama Islam Berbasis Akuntabilitas: Isu dan Permasalahan - Adhi setiyawan (Jurnal Pendidikan Agama Islam, 2007)
Preparation of professional Islam teacher is fondation in national education repair these day. Fruit of fall is not far from place of growing of aphorism word. Student that is with quality comes from teacher that is with quality also. Accountability-based of teacher candidate is bridge in preparation of teacher which competence is area it. Essence and form of its (the implementation is these days still growing and looks for format, the idea and operational). Along repair of image public to teacber profession by government need to be done effort from preparation repair of professional teacher candidat for example in the form of program, perfomance indicator and evaluation system of its the succes. This paper outlines for policy formulations, research and development.